THE ROLE OF ALEXANDER FEYNBERG’S WORK IN UZBEK LITERATURE - Norboyeva Zuhraxon Alijon qizi (TADQIQOTLAR, 2025)
Abstract: This article gives information regarding Alexander Fainberg’s life, artistic endeavors, and cultural legacy. It describes the poet’s contributions to Uzbek literature and culture, especially his translations, poetry collections, and cinematic achievements.